IMPLEMENTASI AMANAT AGUNG BERDASARKAN INJIL MATIUS 28:18-20 BAGI PEMUDA KRISTEN DI GEREJA KEMAH INJIL INDONESIA - Urbanus Toher; Muner Daliman; Hestyn Natal; David Ming (Sekolah Tinggi Teologi Excelsius, 2023)
Every follower of the Lord Jesus is commanded by the Great Commission to go and make followers of Jesus in every nation. Evangelism on a mandate is what this is. However, a large number of God's churches or followers are not committed to executing the evangelistic mandate, which is God's plan to lead everyone to faith in Jesus. Even when discussing evangelism, it seems to be a tough and unpleasant endeavor; it has been demonstrated that evangelical sermons or seminars are not well received; some even contend that evangelism is solely the responsibility of pastors and other members of the clergy. This essay aims to clarify the significance of the great commission in relation to Christians' participation in the effort to plant a new church. The author writes descriptive prose using this technique. The goal of this paper is to: First, emphasize the value of evangelism in local churches; Second, emphasize the significance of every believer's involvement in starting a new church; and Third, encourage every youth to have a clear vision to always be consistent in the church of GKI Indonesia